Role of TGF-β and IL-6 in dendritic cells, Treg and Th17 mediated immune response during experimental cerebral malaria. (December 2016) - Keswani, Tarun; Sarkar, Samrat; Sengupta, Anirban; Bhattacharyya, Arindam
Graphical abstract: Highlights: ECM is associated with the circulating levels of IL-6 and TGF-β. TGF-β exacerbated, whereas delay after IL-6 in malaria immunopathology. Increase in STAT-3 and decrease in STAT-5 expression during PbA infection. Role of CD11c + CD8 + DC subset was observed during PbA infection. Differential expression of mDCs, pDCs, Tregs and Th17 cells during PbA infection. Abstract: The role of cytokines in Plasmodium infection have been extensively investigated, but pro and anti inflammatory cytokines mediated imbalance during malaria immune-pathogenesis is still unrevealed. Malaria is associated with the circulating levels of Interleukin-6 (IL-6) and transforming growth factor β (TGF-β), but association between these two cytokines in immune response remains largely obscured. Using mouse model, we proposed that IL-6 and TGF-β are involved in immune regulation of dendritic cells (DC), regulatory T cells (Treg), T-helper cells (Th17) during P. berghei ANKA ( PbA ) infection. Association between the cytokines and the severity of malaria was established with anti-TGF-β treatment resulting in increased parasitemia and increased immunopathology, whereas; anti-IL-6 treatment delays immunopathology during PbA infection. Further, splenocytes revealed differential alteration of myeloid DC (mDC), plasmocytoid DC (pDC), Treg, Th17 cells following TGF-β and IL-6 neutralization. Interestingly anti-TGF-β reduces CD11c + CD8 + DC expression, whereas anti-IL-6 administration causes a profound increase during PbA infection in Swiss mice. We observed down regulation of TGF-β, IL-10, NFAT, Foxp3, STAT-5 SMAD-3 and upregulation of IL-6, IL-23, IL-17 and STAT-3 in splenocytes during PbA infection. The STAT activity probably plays differential role in induction of Th17 and Treg cells. Interestingly we found increase in STAT-3 and decrease in STAT-5 expression during PbA infection. This pattern of STAT indicates that possibly TGF-β and IL-6 play a crucial role in differentiation of DCs subsets and Treg/Th17 imbalance during experimental cerebral malaria (ECM).